Recent insights into uptake, toxicity, and molecular targets of microplastics and nanoplastics relevant to human health impacts - Khan, Ajmal; Jia, Zhenquan (iScience, 2023)
Microplastics and nanoplastics (M-NPLs) are ubiquitous environmentally, chemically, or mechanically degraded plastic particles. Humans are exposed to M-NPLs of various sizes and types through inhalation of contaminated air, ingestion of contaminated water and food, and other routes. It is estimated that Americans ingest tens of thousands to millions of M-NPLs particles yearly, depending on socioeconomic status, age, and gender. M-NPLs have spurred interest in toxicology because of their abundance, ubiquitous nature, and ability to penetrate bodily and cellular barriers, producing toxicological effects in cells, tissues, organs, and organ systems. The present review paper highlights: (1) The current knowledge in understanding the detrimental effects of M-NPLs in mouse models and human cell lines, (2) cellular organelle localization of M-NPLs, and the underlying uptake mechanisms focusing on endocytosis, (3) the possible pathways involved in M-NPLs toxicity, particularly reactive oxygen species, nuclear factor-erythroid factor 2-related factor 2 (NRF2), Wnt/β-Catenin, Nuclear Factor Kappa B (NF-kB)-regulated inflammation, apoptosis, and autophagy signaling. We also highlight the potential role of M-NPLs in increasing the incubation time, spread, and transport of the COVID-19 virus. Finally, we discuss the future prospects in this field. [Display omitted] Health sciences; Earth sciences; Environmental science; Environmental health; Pollution